Improving Speech Skills of Students Based on Projection of Educational Objectives in Russian Language Classes - Takhirova, Masuda (International Journal of Psychosocial Rehabilitation, 2020)
The article was written with an aim to develop the theoretical foundations for improving the mechanisms for designing educational objectives in the classroom at non-pedagogical universities using the example of teaching the Russian language. The following tasks are posed in the article and appropriate solutions are given: to improve speech skills of the students and the metacognitive components of innovative technologies aimed at the development of speech skills of students based on the design of educational objectives in the context of sociocultural competence; to improve the model and the guidelines for the development of speech skills of students based on the design of educational objectives in the classroom at non-pedagogical universities. The article defines the methods, ways and forms of training and based on them several conclusions were made.